A prozostrodon-like cynodont preserving a natural endocast of the nasal cavity from the Late Triassic of southern Brazil - Kerber, Leonardo (2019)
Here, we reported a specimen (UFRGS-PV 0543T, portion of the skull and partial right dentary) ofa prozotrodontian cynodont that preserves a natural endocast of the nasal cavity. UFRGS-PV 0543Tis tentatively referred to Prozostrodon due to the shape of the snout bones, the height of thehorizontal ramus of the dentary, the position of the Meckelian groove, the presence of pits on thedental lamina. It was collected in the Faixa Nova site (Santa Maria-RS), Carnian, HyperodapedonAZ, the same area than the holotype of P. brasiliensis. In addition to its natural cast, we employedµCT-Scan to access its inner morphology. This specimen preserves the frontal and posterior portionof the nasals. On the ventral region of the skull, the lamina terminalis of the vomer is exposed, butthe secondary palate is not preserved. The natural endocast is formed by the sediment that filled thenasal cavity. On the dorsal surface of the endocast, there is a longitudinal central sulcus, formed bythe median bony ridge. Laterally to this central sulcus, there is a longitudinal sulcus on each side ofthe endocast, formed by the lateral crest. Internally, the vomer shows a dorsal sulcus for thecartilaginous nasal septum extended from the level of the incisive forame up to the laminaterminalis. As in other eucynodonts and basalmost mammaliaforms, UFRGS-PV 05443T does notshow an ossified cribriform plate, but it shows clear limit between the pars posterior of the nasalcapsule and the olfactory bulbs of the brain formed by two oblique ridges connecting to the medianridge on the ventral surface of the frontals. It was possible to reconstruct the anterior portion of theolfactory bulbs, which are oval-shaped, separated by a narrow longitudinal ridge. This Carnianeucynodont shows similarities (wide ethmoidal recess, marked oval-shaped olfactory bulbs) withother Late Triassic probainognathians (Probainognathus, Therioherpeton) and Brasilitherium butdiffers from the latter in the absence of ossified naso- and ethmoturbinals (although this feature was recently considered as dubious), absence of an ossified mesethmoid, and absence of a groove for olfactory nerve on the lateral surface of the medial ridge. [FAPERGS 17/2551-0000816-2]